Construindo a autonomia: o caso da Associação dos Guardiões das Sementes Crioulas de Ibarama/RS - Cassol, Kelly Perlin (2013)
This research enquires how family farmers who are part of the Association of Creole Seed keepers of Ibarama, RS, rescue their traditional knowledge about the production of the creole corn seed, and how these farmers learn the production's techniques, through institutions that develop agricultural education activities, such as the Federal University of Santa Maria. The research also intends to investigate how this rescue process of knowledge and construction of the knowledge interfere in the organization of the units of production and reproduction of the family farming and the way of life of these individuals. To answer its objectives, the research shows that a qualitative approach, was developed through participatory research, therefore, the research count on a methodological hybrid focused in observation and semi-structured interviews that were realized with participating farmers of the association, the technical of the institutions EMATER and UFSM and also the current priest of the local Catholic church. After the interviews, we can understand how the development of the formalization of the Association was built, what are its achievements, limits and future prospects, as well as is possible to observe the role of the Federal University of Santa Maria as a partner in the Association's activities. Finally, highlights the important role of the Association front the society, with the conservation and rescue of the creole seeds, for this to be an act of valuing life and traditional knowledge.